MO697TUBERCULOUS PERITONITIS WITH HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS IN A PATIENT ON CONTINUOUS AMBULATORY PERITONEAL DIALYSIS: A CASE REPORT. (29th May 2021) - Dassi, Manisha; JhaJhria, Anil; Aggarwal, Neeru; Jha, Lakshmikant
Abstract: Background and Aims: Tuberculosis is a leading cause of morbidity and mortality worldwide. Tuberculous peritonitis in patients on Continuous Ambulatory Peritoneal Dialysis (CAPD), though uncommon, has been reported from different parts of the world. Hemophagocytic lymphohistiocytosis (HLH) is a rare systemic inflammatory disorder characterized by uncontrolled proliferation of lymphocytes & histiocytes and is reported to have high mortality. Secondary forms of HLH have been described for various diseases. Here, we report a case of HLH secondary to Tuberculous peritonitis in a patient of End Stage Renal Disease (ESRD) on CAPD. Method: A 49 years old male ESRD patient, on CAPD presented with peritonitis and was initially managed with antibiotics. He required catheter explantation in view of refractory peritonitis and was switched to haemodialysis. The patient continued to have low grade fever, yellowish discharge from infra-umbilical CAPD catheter explantation surgical wound along with lower abdominal pain & tenderness. He was lost to follow up and presented again after 1 month with fever, weight loss, multiple cutaneous ecchymotic spots and copious amount of yellowish discharge from infra-umbilical surgical wound. On examination, he had fever, conjunctival pallor, hepatosplenomegaly and a 5 cm infra-umbilical midline poorly healed discharging surgical scar with surrounding skin erythema and induration. Blood investigations revealed Hb 5.1 gm/dl, TLC 1500/uL, Plts 32000/uL, Ferritin 1053 ng/ml, TG 350 mg/dl, LDH 650 U/l, Bil T/D 1.3/1.0 mg/dl, OT/PT 160/174 IU/l, ALP 219 U/l, GGT 238 U/l, TP/Alb 5.2/2.5 gm/dl, APTT C/T 27.9/63.0, INR 1.27. NCCT abdomen revealed hepatosplenomegaly, loculated collection in right subphrenic region extending into the abdominal and pelvic cavity, anterior abdominal wall defect infero-right lateral to the umbilicus and generalised increased density in mesenteric fat. Diagnostic sub-phrenic fluid Aspirate analysis revealed a yellow turbid fluid with TLC 22300, ADA 106 U/L and positive Real Time PCR for Mycobacterium tuberculosis complex. Aspirate pyogenic and fungal cultures were sterile. Bone marrow evaluation revealed marked degree of histiocytic hemophagocytosis. Patient fulfilled six out of eight criteria for diagnosis of HLH. He was started on Anti Tubercular Treatment along with dexamethasone. He gradually became afebrile with resolution of infra-umbilical wound discharge, improvement in clinical and laboratory parameters. Results: We report a case of HLH secondary to Tuberculous peritonitis in a patient of ESRD. The patient was on CAPD and required catheter explantation in view of Refractory peritonitis. Despite explantation and adequate antibiotics, he continued to have fever, discharge from surgical wound, pain abdomen, weight loss and poor appetite. Further evaluation revealed evidence of Tuberculous Peritonitis. In addition, the patient fulfilled six out of eight criteria for diagnosis of HLH. The patient was managed with Anti Tubercular Treatment along with Dexamethasone and he showed a gradual improvement in overall clinical and laboratory parameters. Conclusion: Secondary HLH may occur after Tuberculous peritonitis in patient of ESRD on CAPD. Refractory peritonitis with hyperferritenemia, cytopenias, hypertriglyceridemia should raise the suspicion for HLH. Timely identification and treatment of HLH may improve patient outcomes.